Sensory processing sensitivity - Rajić, Isidora (Psihološka istraživanja, 2024)
The main aim of this review article is to describe the sensory processing sensitivity trait (SPS). People with this trait are highly sensitive individuals and the scientific literature states that they make up 20% to 30% of the general population. Theories that originally explained the high sensitivity of a certain segment of the population are described, the results of the studies that explored the discriminant validity of the Highly Sensitive Person Scale, the studies that examined the relationships between the SPS trait and personality dimensions, and the studies on the quality of mental health of highly sensitive individuals. Although there is an increasing amount of research on highly sensitive people worldwide, this is not the case in our region, and experts (psychologists, psychotherapists and psychiatrists) in Serbia and the region are largely unfamiliar with this trait. Consequently, it is possible to confuse the SPS trait with a personality dimension (neuroticism, introversion, shyness, etc.) or to diagnose a disorder (autism, attention deficit hyperactivity disorder, etc.) in highly sensitive individuals. In addition, the increasing number of newspaper articles on various internet portals about highly sensitive people means that high sensitivity in our region is only described through the lens of popular psychology. All this can lead to a misunderstanding of this scientific construct. Considering that scientific literature indicates that approximately a quarter of the general population is highly sensitive, it is extremely important that professionals are more familiar with sensory processing sensitivity trait.